Variações florísticas e estruturais de um remanescente de floresta ombrófila mista montana em Nova Prata - RS - Callegaro, Rafael Marian (2012)
This work aimed to analyze floristic and structure variations in a Montane Mixed Ombrophylous Forest remnant, in the county of Nova Prata, RS. It was inventoried 71 parcels with dimensions of 10 x 100 m, using the process of systematic sampling in Two Stages. It were identified and measured all individuals with circumference at breast height ≥ 30,0 cm. The dissertation was divided into two chapters, with specific objectives to analyze the presence of floristic groups (Chapter I) and diagnostic and diagnose structural variations between clusters (Chapter II). The plots were classified by cluster analysis, using the Ward connection method. The plots were classified into four distinct floristic groups that present differences in specific diversity, composition and floristic similarity. The group 3 included the largest area of forest remaining and it had the highest diversity values and species number between groups, and greater floristic similarity with the forest in general. It was observed that different species dominate ecological groups in relation to the structure, favoring the development of specific populations. The aggregate (clustered) distribution pattern was the main pattern of spatial distribution of species obtained in the groups, indicating that the species forming denser spots in the vegetation. The diameter and hypsometric structures proved to be different between groups indicating they have good capacity for renewal and a denser canopy bottom. In summary, the floristic groups of the Montane Mixed Ombrophylous Forest remnant had floristic and structural variations. These variations evidence the need to consider different arboreous communities in the case of an intervention.